Numerical study of geogrid-reinforced segmental earth retaining wall - Ouassim Rahmouni; Abdelhak Mabrouki; Djamel Benmeddour; Mekki Mellas (Journal of Applied Engineering Science and Technology, 2015)
Geogrid-reinforced soil segmental retaining walls have gained wide popularity because of their ease of installation and quick construction. This paper focuses on the numerical analysis using the FLAC3D (Fast Lagrangian Analysis of Continua in 3 Dimensions), the influence of the inclined blocs on the behavior of geogrid-reinforced soil segmental retaining walls. The results show that the inclination of the segmental blocks influences the shear stress transmitted to the blocks, the lateral displacement, the tensile loads and the strains in the geogrid layers.